Allosteric links between the hydrophilic N‐terminus and transmembrane core of human Na+/H+ antiporter NHA2. (16th November 2022) - Velázquez, Diego; Průša, Vojtěch; Masrati, Gal; Yariv, Elon; Sychrova, Hana; Ben‐Tal, Nir; Zimmermannova, Olga
Abstract: The human Na + /H + antiporter NHA2 ( SLC9B2 ) transports Na + or Li + across the plasma membrane in exchange for protons, and is implicated in various pathologies. It is a 537 amino acids protein with an 82 residues long hydrophilic cytoplasmic N‐terminus followed by a transmembrane part comprising 14 transmembrane helices. We optimized the functional expression of Hs NHA2 in the plasma membrane of a salt‐sensitive Saccharomyces cerevisiae strain and characterized in vivo a set of mutated or truncated versions of Hs NHA2 in terms of their substrate specificity, transport activity, localization, and protein stability. We identified a highly conserved proline 246, located in the core of the protein, as being crucial for ion selectivity. The replacement of P246 with serine or threonine resulted in antiporters with altered substrate specificity that were not only highly active at acidic pH 4.0 (like the native antiporter), but also at neutral pH. P246T/S versions also exhibited increased resistance to the Hs NHA2‐specific inhibitor phloretin. We experimentally proved that a putative salt bridge between E215 and R432 is important for antiporter function, but also structural integrity. Truncations of the first 50–70 residues of the N‐terminus doubled the transport activity of Hs NHA2, while changes in the charge at positions E47, E56, K57, or K58 decreased the antiporter's transport activity. Thus, the hydrophilic N‐terminal part of the protein appears to allosterically auto‐inhibit cation transport of Hs NHA2. Our data also show this in vivo approach to be useful for a rapid screening of SNP's effect on Hs NHA2 activity.